A Universal Aqueous Conductive Binder for Flexible Electrodes. (17th June 2021) - Wang, Hanwei; Fu, Jinzhou; Wang, Chao; Zhang, Ruiwang; Yang, Yushan; Li, Yingying; Li, Caicai; Sun, Qingfeng; Li, Huiqiao; Zhai, Tianyou
Abstract: The development of wearable electronics has led to new requirements for flexible and high‐energy batteries. However, the conventional polyvinylidene fluoride binder fails in the manufacture of high‐loaded and thick battery electrodes owing to its insufficient adhesiveness and electronic insulation, let alone for flexible devices. Furthermore, organic processing is expensive and not eco‐friendly. Herein, the authors report a novel aqueous conductive binder made of carbon nanotubes interwoven in cellulose nanosheets, successfully satisfying the fabrication of flexible yet high‐strength electrodes for universal active materials of different sizes, morphologies, and negative‐to‐positive working potentials, with a high mass loading of up to ≈ 90 mg cm −2 . The conductive binder has an ultrathin 2D‐reticular nanosheet structure that forms continuous conductive skeletons in electrodes to segregate and warp active particles via a robust "face‐to‐point" bonding mode, allowing the fabricated electrodes to have remarkable flexibility and excellent mechanical integrity even under various external forces and excessive electrolyte erosion. Flexible LCO cathodes with a mass loading of > 30 mg cm −2 as a case study exhibit high mechanical strength (> 20 MPa) and can easily achieve an ultrahigh areal capacity of 12.1 mAh cm −2 . This cellulose‐based binder system is ideal for advanced high‐performance functional devices, especially for flexible and high‐energy batteries. Abstract : A novel, green, and conductive water‐based binder made of carbon nanotubes interwoven in cellulose nanosheets is developed, achieving highly effective bonding of various commercial cathode and anode materials for flexible, high‐strength, and high‐loading electrodes (up to ≈90 mg cm −2 ). This cellulose‐based binder system is ideal for advanced high‐performance functional devices, especially for flexible batteries and high‐energy batteries.